Selective separation and determination of the synthetic colorants in beverages by magnetic solid‐phase dispersion extraction based on a Fe3O4/reduced graphene oxide nanocomposite followed by high‐performance liquid chromatography with diode array detection. Issue 12 (15th May 2015) - Wang, Xi; Chen, Ning; Han, Qing; Yang, Zaiyue; Wu, Jinhua; Xue, Cheng; Hong, Junli; Zhou, Xuemin; Jiang, Huijun
<x xml:space="preserve">Abstract</x> A facile adsorbent, a nanocomposite of Fe3O4 and reduced graphene oxide, was fabricated for the selective separation and enrichment of synthetic aromatic azo colorants by magnetic solid‐phase dispersion extraction. The nanocomposite was synthesized in a one‐step reduction reaction and characterized by atomic force microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, X‐ray diffraction and Brunauer–Emmett–Teller analysis. The colorants in beverages were quickly adsorbed onto the surface of the nanocomposite with strong π–π interactions between colorants and reduced graphene oxide, and separated with the assistance of an external magnetic field. Moreover, the four colorants in beverages were detected at different wavelengths by high performance liquid chromatography with diode array detection. A linear dependence of peak area was obtained over 0.05–10 μg/mL with the limits of detection of 10.02, 11.90, 10.41, 15.91 ng/mL for tartrazine, allure red, amaranth, and new coccine, respectively (signal to noise = 3). The recoveries for the spiked colorants were in the range of 88.95–95.89% with the relative standard deviation less than 2.66%. The results indicated that the nanocomposite of Fe3O4 and reduced graphene oxide could be used as an excellent selective adsorbent for aromatic compounds and has potential applications in sample pretreatment.